(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
It was observed that a 30-day exposure to noise resulted in significant decreases in the total number of erythrocytes, reticulocytes, and hemoglobin levels, along with a marked reduction in blood oxygen capacity. In contrast, the 30-day combined exposure to noise and licorice root (Glycyrrhiza glabra L.) led to a significant increase in these hematological parameters, thereby promoting homeostasis under conditions of prolonged exposure to noise as a stress factor.